Description de l’implantation d’un programme de prévention des problèmes de comportement à l’adolescence - Haggerty, Kevin; Catalano, Richard; Harachi, Tracy; Abbott, Bob (Criminologie, 1998)
This paper describes a comprehensive approach to preventing a variety of adolescent problem behaviors, including drug use, delinquency, violence, school dropout and teenage pregnancy. The experimental intervention is designed to enhance protection and reduce risk for these adolescent problem behaviors. The project, Raising Healthy Children (RHC), extends earlier work conducted in the Seattle Social Development Project (Hawkins, Catalano, Morrison, O'Donnell, Abbott & Day, 1992; O'Donnell, Hawkins, Catalano, Abbott & Day, 1995). The interventions are guided by the Social Development Model (Catalano & Hawkins, 1996), a theory that explains the development of both prosocial and antisocial behavior. Because risk and protective factors for these problems are found in multiple social domains, the interventions address these factors through developmentally appropriate strategies in the three major socializing institutions, the family, school, and peer groups. The "school intervention strategy " provides a series of instructional improvement workshops and classroom coaching designed to increase student's commitment and attachment to school while reducing academic failure. The "family intervention strategy " provides parenting workshops and home-based services to increase parents' skills in child rearing, to increase attachment and commitment to the family while decreasing family management problems. The "peer intervention strategy" provides children the opportunity to learn and practice social and emotional skills in the classroom and in social situations. These combined strategies are described in detail. Preliminary analyses reveal significant effects of these strategies on reducing early risk and increasing protection.